Brand personality of two beverages categories - Liang, Johan; Lee, Thomas; Phau, Ian (International Management Development Association, 2011)
This study focuses on the 42 traits of brand personality (Aaker 1997) of six drink brands spanning across two drink segments – fizzy drink and mineral water, and measure the congruity of the brands’ personalities (five dimension) to the consumer (drinker) of those brands. A number of implications for businesses will be discussed, suggestions for future research are reviewed and the main contributions of the study will also be delineated.